Pengaruh Pemberian Nugget Ikan Kembung dan Daun Kelor Terhadap Peningkatan Kadar Hemoglobin Pada Remaja Putri di Madrasah Aliyah Nurul Falah Kecamatan Pangkalanbaru - Sari, Winda; Aprilia, Maya; Puspandari, Hendriana (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2024)
Background: Anemia is a condition in which a person's body experiences a decrease or the number of red blood cells in the body is below normal limits. Several factors that cause anemia experienced by adolescents are lack of knowledge of anemia and nutritional intake which affects the choice of nutritious food consumption, not being used to breakfast, the habit of drinking tea and coffee which inhibits the absorption of iron in the body, and intake of several nutrients that are less than the AKG, iron intake is deficient and adolescent girls are not routinely consuming Fe tablets. Purpose: The study aims to determine the effect of giving mackerel nuggets and moringa leaves on increasing hemoglobin levels in adolescent girls at Madrasah Aliyah Nurul Falah. Methods: This study is a quasi-experimental study. With a One Group Pre test-Post test Design research design. The study was conducted from February - May 2024 with a sample of 54 respondents. Results: The results of the dependent T-Test showed that there was a difference in the average increase in hemoglobin levels with a p-value of 0.000 (<0.05). Conclusion: There is an effect of giving mackerel nuggets and moringa leaves on increasing hemoglobin levels in adolescent girls.